Characterizing the spatio-temporal dynamics of NTL-derived anthropogenic intensity around urban lakes in China - Jie Li; Xiaomei Fan; Qicheng Liu; Chenyu Fan; Hui Zhang; Congsheng Fu; Lei Wang; Kai Liu; Chunqiao Song (Remote Sensing Applications: Society and Environment, 2026)

Contrasting effects of extreme weather events on carbon uptake and emissions in rice and wheat ecosystems - Ye Xia; Congsheng Fu; Aimin Liao; Huawu Wu; Haohao Wu; Haixia Zhang; Jianyao Chen (Agricultural and Forest Meteorology, 2026)

Exploring the contrasting lake CO2 fluxes and influencing variables in four large shallow subtropical lakes with different hydrological connectivity - Zichun Zhu; Haohao Wu; Ke Jiang; Qitao Xiao; Huawu Wu; Haixia Zhang; Ye Xia; Congsheng Fu (Journal of Environmental Management, 2025)

Comparing rainfall partitioning between leafed and leafless periods in an eastern Chinese subtropical deciduous forest: Insights from inter-event and intra-event scale analysis - Haixia Zhang; Huawu Wu; Aimin Liao; Haohao Wu; Yue Wang; Jing Li; Congsheng Fu (Journal of Hydrology, 2025)

Identifying seasonal sources and processes controlling nitrate in a typical reservoir-type headwater watershed of Eastern China using stable isotopes - Mengyao Ding; Huawu Wu; Haixia Zhang; Qing Zhu; Ruiyu Lei; Kaiwen Li; Hongxiang Fan; Jing Li; Congsheng Fu (Agriculture, Ecosystems & Environment, 2025)

A global perspective on the development and application of glacio-hydrological model - Chengde Yang; Xin Wang; Shichang Kang; Min Xu; Yong Zhang; Junfeng Wei; Congsheng Fu (Journal of Hydrology, 2025)

Influences of extreme weather events on the carbon to nitrogen ratios of major staple crops - Ye Xia; Congsheng Fu; Aimin Liao; Huawu Wu; Haohao Wu; Haixia Zhang; Xibao Xu; Jianyao Chen (Science of The Total Environment, 2025)

Drought‐Induced Weakening of Temperature Control on Ecosystem Carbon Uptake Across Northern Lands - Haohao Wu; Congsheng Fu; Kailiang Yu; Philippe Ciais; Ashley Ballantyne; Zhihua Liu; Brendan M. Rogers; Shilong Piao; Yizhao Chen; Lingling Zhang; Huawu Wu; Xingwang Fan; et al. (Global Change Biology, 2025)
Rapid warming in northern lands has led to increased ecosystem carbon uptake. It remains unclear, however, whether and how the beneficial effects of warming on carbon uptake will continue with climate change. Moreover, the role played by water stress in temperature control on ecosystem carbon uptake remains highly uncertain. Here, we systematically explored the trend in the temperature control on gross primary production (measured by “ S GPP‐TAS ”) across northern lands (> 15°N) using a standardized multiple regression approach by controlling other covarying factors. We estimated S GPP‐TAS using three types of GPP datasets: four satellite‐derived GPP datasets, FLUXNET tower observed GPP datasets, and GPP outputs from nine CMIP6 models. Our analysis revealed a significant positive‐to‐negative transition around the year 2000 in the trend of S GPP‐TAS . This transition was primarily driven by synchronized changes in soil water content over time and space. The S GPP‐TAS trend transition covered about 32% of northern lands, especially in grasslands and coniferous forests where leaf water mediation and structural overshoot accelerated the drought‐induced transition, respectively. In the future, widespread negative S GPP‐TAS trends are projected in northern lands corresponding with decreasing soil water availability. These findings highlight the shrinking temperature control on northern land carbon uptake in a warmer and drier climate.

Optimum urban runoff pollution control based on dynamic load calculation and effective control units identification – a case study in a highly urbanized basin in China - Xiao Wang; Yingdong Tang; Fengshan Zhang; Congsheng Fu; Mingzhi Zhao (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Reproducing surface water isoscapes of δ18O and δ2H across China: A machine learning approach - Huawu Wu; Hongxiang Fan; Jing Li; Fu-Jun Yue; Ergang Lian; Congsheng Fu; Ruiyu Lei; Mengyao Ding; Jinzhao Liu; Xiao-Yan Li (Journal of Hydrology, 2024)

Exploring recharge mechanisms of soil water in the thick unsaturated zone using water isotopes in the North China Plain - Huawu Wu; Fan Song; Leilei Min; Jing Li; Yanjun Shen; Yanan Huang; Hongxiang Fan; Jinzhao Liu; Congsheng Fu (CATENA, 2024)

Improvement of streamflow simulation by combining physically hydrological model with deep learning methods in data-scarce glacial river basin - Chengde Yang; Min Xu; Shichang Kang; Congsheng Fu; Didi Hu (Journal of Hydrology, 2023)

Atmospheric processes control the stable isotopic variability of precipitation in the middle–lower reaches of the Yangtze River Basin, East Asian monsoon region - Huawu Wu; Hongxiang Fan; Ruiyu Lei; Chijun Sun; Shengjie Wang; Haohao Wu; Congsheng Fu (Journal of Hydrology, 2023)

Exploring the effects of extreme weather events on methane emissions from croplands: A study combining site and global modeling - Ye Xia; Congsheng Fu; Huawu Wu; Haohao Wu; Haixia Zhang; Aimin Liao; Jianyao Chen (Agricultural and Forest Meteorology, 2023)

Hydraulic redistribution affects modeled carbon cycling via soil microbial activity and suppressed fire - Congsheng Fu; Guiling Wang; Kenneth Bible; Michael L. Goulden; Scott R. Saleska; Russell L. Scott; Zoe G. Cardon (Global Change Biology, 2018)
Hydraulic redistribution (HR) of water from moist to drier soils, through plant roots, occurs world‐wide in seasonally dry ecosystems. Although the influence of HR on landscape hydrology and plant water use has been amply demonstrated, HR's effects on microbe‐controlled processes sensitive to soil moisture, including carbon and nutrient cycling at ecosystem scales, remain difficult to observe in the field and have not been integrated into a predictive framework. We incorporated a representation of HR into the Community Land Model (CLM4.5) and found the new model improved predictions of water, energy, and system‐scale carbon fluxes observed by eddy covariance at four seasonally dry yet ecologically diverse temperate and tropical AmeriFlux sites. Modeled plant productivity and microbial activities were differentially stimulated by upward HR, resulting at times in increased plant demand outstripping increased nutrient supply. Modeled plant productivity and microbial activities were diminished by downward HR. Overall, inclusion of HR tended to increase modeled annual ecosystem uptake of CO 2 (or reduce annual CO 2 release to the atmosphere). Moreover, engagement of CLM4.5′s ground‐truthed fire module indicated that though HR increased modeled fuel load at all four sites, upward HR also moistened surface soil and hydrated vegetation sufficiently to limit the modeled spread of dry season fire and concomitant very large CO 2 emissions to the atmosphere. Historically, fire has been a dominant ecological force in many seasonally dry ecosystems, and intensification of soil drought and altered precipitation regimes are expected for seasonally dry ecosystems in the future. HR may play an increasingly important role mitigating development of extreme soil water potential gradients and associated limitations on plant and soil microbial activities, and may inhibit the spread of fire in seasonally dry ecosystems.

Combined Effects of Solar Activity and El Niño on Hydrologic Patterns in the Yoshino River Basin, Japan - Linyao Dong; Congsheng Fu; Jigen Liu; Pingcang Zhang (Water Resources Management, 2018)

Analysis of groundwater-level fluctuation in a coastal confined aquifer induced by sea-level variation - Linyao Dong; Jianyao Chen; Congsheng Fu; Huabo Jiang (Hydrogeology Journal, 2012)